Penerapan Konsep Cyber Notary dalam Praktek Hukum di Indonesia - Krisna Bayumurti; Novan Perdana; Ronan Steven Tjandra (Jurnal Hukum Lex Generalis, 2025)
The increasing demand for technological integration in legal practices has introduced the concept of cyber notary, which enables notaries to perform their duties electronically. This research examines the feasibility of implementing the cyber notary concept within Indonesia's legal framework, focusing on its boundaries and challenges. Using a normative legal research methodology, this study analyzes statutory and conceptual approaches to identify gaps in existing regulations. The findings reveal that while laws such as the UUJN-P and UU ITE provide initial support, significant barriers remain, particularly concerning the physical presence requirement and the recognition of electronic signatures as equivalent to traditional signatures. Consequently, this study highlights the urgent need for regulatory adjustments to enable the cyber notary concept to align with the principles of legal certainty and authenticity. The implementation of cyber notary practices can enhance efficiency and accessibility, provided that foundational legal structures are strengthened.